Presentation of a New AMS Facility at the Instituto de Datación y Arqueometría ( InDyA) Jujuy Argentina - Kulemeyer, Julio José (2019)
A 1 MV AMS system will be installed at the Instituto de Datación y Arqueometría (INDyA), located in the province of Jujuy, Argentina. InDyA is a consortium between the Government of Jujuy, the Jujuy National University, the Tucumán National University and the National Council of Scientific and Technical Research (CONICET). Within the framework of the Program of InterInstitutional Centers on Strategic Issues promoted by the Secretary of Science, Technology and Productive Innovation, we have acquired an AMS system developed by HVEE that will be used to measure 14C, 10Be and 26Al. The system comprises a Tandetron accelerator with 1 MV terminal voltage capability and features two analyzing magnets in the high-energy spectrometer which can be compared to the more commonly configuration with just one analyzing magnet. The additional magnet results in optimal performance for low-background applications. With the collaboration of the National Atomic Energy Commission, the instrument will be installed in Palpalá, province of Jujuy.